Comparative Outcomes of Salvage Retzius-Sparing versus Standard Robotic Prostatectomy: An International, Multi-Surgeon Series. Issue 5 (28th November 2021) - Kowalczyk, Keith J.; Madi, Rabii H.; Eden, Christopher G.; Sooriakumaran, Prasanna; Fransis, Karen; Raskin, Yannic; Joniau, Steven; Johnson, Scott; Jacobsohn, Kenneth; Galfano, Antonio; Bocciardi, Aldo M.; Hwang, Jonathan; et al.
Abstract : Purpose: Salvage radical prostatectomy is rare due to the risk of postoperative complications. We compare salvage Retzius-sparing robotic assisted radical prostatectomy (SRS-RARP) with salvage standard robotic assisted radical prostatectomy (SS-RARP). Materials and Methods: A total of 72 patients across 9 centers were identified (40 SRS-RARP vs 32 SS-RARP). Demographics, perioperative data, and pathological and functional outcomes were compared using Student's t-test and ANOVA. Cox proportional hazard models and Kaplan-Meier curves were constructed to assess risk of incontinence and time to continence. Linear regression models were constructed to investigate postoperative pad use and console time. Results: Median followup was 23 vs 36 months for SRS-RARP vs SS-RARP. Console time and estimated blood loss favored SRS-RARP. There were no differences in complication rates or oncologic outcomes. SRS-RARP had improved continence (78.4% vs 43.8%, p <0.001 for 0–1 pad, 54.1% vs 6.3%, p <0.001 for 0 pad), lower pads per day (0.57 vs 2.03, p <0.001), and earlier return to continence (median 47 vs 180 days, p=0.008). SRS-RARP was associated with decreased incontinence defined as >0–1 pad (HR 0.28, 95% CI 0.10–0.79, p=0.016), although not when defined as >0 pad (HR 0.56, 95% CI 0.31–1.01, p=0.053). On adjusted analysis SRS-RARP was associated with decreased pads per day. Lymph node dissection and primary treatment with stereotactic body radiation therapy were associated with longer console time. Conclusions: SRS-RARP is a feasible salvage option with significantly improved urinary function outcomes. This may warrant increased utilization of SRS-RARP to manage men who fail nonsurgical primary treatment for prostate cancer.